Pertumbuhan Bibit Anggur Prabu Bestari Asal Okulasi pada Berbagai Campuran dan Kandungan Air Media Tanam - I GUSTI ALIT GUNADI; I KETUT SUMIARTHA (Fakultas Pertanian Universitas Udayana, 2019)
The Growth and Development of the Prabu Bestari Grape Seedling on Various Compositions and Water Content of Growing Media. The growth and development of the grape seedling influenced by the presence of solar and ground water energy. Prabu Bestari is a originally variety introduced by Balitjestro from Australia after being assembled with the selection process. The need for this variety of agroclimates is in accordance with the North Bali region as a production center. The bud break in grape plant can be affected by condition of plant media during the seedling procession. Shoot failure in grapes can be caused by the condition of the planting medium in the nursery process. This study aims to determine the growth of grape seedlings that are treated with the use of planting media (soil, soil, chaff, soil + cocopeat, and soil compost) 1: 1 (v / v) mixture ratio. The planting media treatment will be combined with different water content (100%, 75%, and 50% of the field capacity conditions). The study was conducted in a green house at the Experimental Station of Faculty of Agriculture Udayana University from May to August 2018. The research used factorial method (4 x 3) which was designed randomly in groups with three replications. The results showed no interaction on all parameters observed. Increasing length of tendrils (148.16 cm) and number of leaves (26.58 strands) looks better with increasing groundwater content up to 100% of field capacity, whereas the resistant mixture + compost gave the highest increase in tendril length (131.91 cm) and the number of leaves (26.56 pieces). The highest chlorophyll content of the leaves reached 28.68 SPAD unit in a mixture of soil + compost treatment and the lowest was in land use + cocopeat with 18.99 SPAD unit. While the highest leaf chlorophyll content due to water content treatment was shown in 100% of field capacity treatment of 27.84 SPAD unit.